Plating manifesto (II): the art and science of plating - Spence, C; Piqueras-Fiszman, B; Michel, C; Deroy, O (BioMed Central, 2014)
It is well known that people serve themselves more, not to mention eat more, when dining from larger bowls and plates than from smaller ones. But what about the other visual qualities of the plateware? Does the colour, shape and finish also influence a diner’s behaviour? How important are these extrinsic visual properties, or even the visual arrangement of the elements on the plate itself, in terms of modulating a diner’s eating behaviours and experiences? At a time when so much is known about the influence of the colour of individual food products on taste and flavour perception, and when so many modernist restaurants are using an increasingly eclectic range of visual designs for their dishes, there has been surprisingly little scientific research on how the more complex visual properties and arrangement of food presentations may affect the diner. Below, we argue that the exploration of these effects constitutes the next natural step in an increasingly fruitful interdisciplinary collaboration between chefs, psychologists, sensory scientists and designers. The most important research questions, then, are to identify the kinds of effects that the presentation style has on the multisensory consumption experiences and behaviours of diners, and to study the interactions between the different visual cues that are provided. Taken together, the evidence reviewed here helps to emphasize the fact that getting both the plateware and the plating right constitute surprisingly important components to sublimate the flavours of the food, in the delivery and experience of a great meal.